A Brief Note on Online Learning - cut raudhatul miski (Lembaga Anotero Scientific Pekanbaru, 2021)
The pandemic of Covid 19 has forced the writer and also whole teachers worldwide to teach online, in which it was, for the writer herself, was seldom to do. Though, it was reported, in some developing countries, online education is rarely used before the pandemic. Despite, the teaching and the learning should be maintained. This paper provides teachers with elligible information on what is online education in which online learning or online teaching is recognized. This will helps teachers to figure out what online education is, especially online learning, what should be there in online learning and how technology benefits the online teaching and learning in order to support students’ learning. The writer hopes this article can contribute somewhat. KEYWORDS: Brief Note, Online learning